The Integration of Human Rights Principles in Nigeria's Counterterrorism Framework: A Pathway to Sustainable Security - KALU, Benjamin Okezie (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
This paper presents a comprehensive analysis of the ongoing integration of human rights principles within Nigeria's counterterrorism architecture. Operating in a complex and high-threat environment, the Nigerian government has undertaken significant measures to combat terrorist organizations like Boko Haram and the Islamic State in West Africa Province (ISWAP). This study acknowledges the formidable challenges faced by security forces while exploring how a deepened commitment to international human rights and humanitarian law standards can serve as a force multiplier, enhancing operational effectiveness and strengthening the vital bond between the state and its citizenry. The paper examines specific operational incidents not as indictments, but as complex case studies from which valuable lessons on procedure, coordination, and community engagement have been and can continue to be learned. It provides a detailed review of Nigeria's robust legal and institutional frameworks, highlighting progressive legislation and ongoing reform initiatives within the security sector. Furthermore, the analysis considers the strategic imperative of winning public trust as a cornerstone of effective counterinsurgency. The paper concludes that the continued and deliberate alignment of security operations with human rights norms is not merely a legal obligation but a strategic necessity for achieving lasting peace and stability. Recommendations are offered in a constructive spirit to support and build upon the government's existing efforts, aiming to fortify Nigeria's counterterrorism model into one that is both profoundly effective and unwavering in its protection of fundamental freedoms.